Content management based on multi-agent system for collaborative design. (30th March 2009) - Gomes, Samuel; Monticolo, Davy; Hilaire, Vincent; Eynard, Benoit
Collaborative design methods are increasingly integrated into industrial systems in order to reduce costs and lead time, but also to improve product quality and value. Design tasks involve many actors throughout the product lifecycle, which starts with product requirements, functional specification, product modelling, manufacturing and ends with its recycling. Software supporting collaborative design, such as Product Lifecycle Management (PLM) systems, is needed to help design team members in their project tasks. The Atelier Cooperatif de Suivi de Projet in French (ACSP) platform is a web-based PLM system. It supports the design team members in carrying out collaborative activities in product-process-design projects. An improvement of the ACSP platform has been proposed by introducing multi-agent systems at several levels of the ACSP architecture. This improvement is based on the Role, Interaction and Organisation methodology and on many FIPA specifications. By implementation of multi-agent systems for content and knowledge management in collaborative engineering, one can develop autonomy, reactivity, pro-activity and social ability in the man?machine relationships.